Hubungan Kebersihan Ruang Belajar Dengan Kenyamanan Menuntut Ilmu Santri - Ageng saepudin kanda; Yulia agustin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to determine the cleanliness of the study room environment at the Daarul Haliim Bandung Islamic Boarding School and to determine the role of students in maintaining the cleanliness of the study room environment and to determine the effect of classroom cleanliness on students' learning concentration abilities. This research is descriptive in nature, namely studies resulting from natural or man-made phenomena. Completion of this scientific work was assisted by several mass media, namely electronic (Internet), case studies (methods for collecting the necessary information, drawing samples into certain related sampling units and studying more in-depth interviews with samples). The results of this research show that cleanliness greatly influences the students' learning process because a dirty environment will affect comfort and focus in teaching and learning activities. The benefits of having a clean boarding school environment are avoiding infectious diseases which often occur in students, comfort in teaching and learning, the students' level of focus will increase in absorbing the material provided by the ustadz/ustadzh and the environment will be beautiful and beautiful and have good air quality. for health.